Digital nerve blocks: A systematic review and meta‐analysis. Issue 4 (1st July 2022) - Borbón, Tiffany Y.; Qu, Pingping; Coleman‐Satterfield, T. Tausala; Kearney, Ryan; Klein, Eileen J.
Abstract: Study objective: Digital nerve blocks (DNBs) provide local anesthesia for minor procedures of the digits. Several DNB techniques have been described, but it is unclear which technique provides adequate anesthesia with the least pain. DNB techniques can be grouped into a dorsal approach, which requires 2 injections, versus 3 different types of volar approaches, which require a single injection. We performed a meta‐analysis to compare DNB techniques with respect to time to anesthesia (TTA), duration of anesthesia (DOA), and pain of injection. We also reviewed data on degree and distribution of anesthesia and discuss the techniques preferred by study participants and clinicians performing injections. Data Sources: We searched MEDLINE, EMBASE, and CENTRAL databases with terms "digital block, " "digital nerve block, " "local anesthetic, " "local anesthesia, " "lidocaine, " and/or "bupivacaine." Study Selection: Randomized controlled trials (RCTs) were prioritized, though high‐quality prospective cohort studies were also eligible. All included studies evaluated DNB techniques or anesthetics. There were 23 papers (21 RCTs, 2 prospective descriptive studies) included. Data Extraction: DNBs studied included dorsal ring block, traditional dorsal block, transthecal block, modified transthecal block, and volar subcutaneous digital blocks. Outcomes measured included TTA, DOA, pain of injection scores, and degree of anesthesia. Results: Overall, mean TTA was 4.5 minutes (95% confidence interval [CI] 3.5, 5.6), mean DOA was 187 minutes (95% CI 104.3, 269.7), and mean pain score was 2.1 out of 10 (95% CI 1.3, 2.8) without significant differences between studies or techniques. Conclusions: There were no significant differences in the outcomes of TTA, DOA, and pain of injection between different DNB techniques. Single‐injection volar approaches may be preferred by participants and clinicians over dorsal approaches that require 2 injections, particularly with respect to pain. However, 2‐injection dorsal approaches may have better coverage of the proximal dorsal surface based on degree and distribution of anesthesia.